A life-and-death struggle: interaction of insects with entomopathogenic fungi across various infection stages - Ma, Meiqi; Luo, Jing; Li, Chong; Eleftherianos, Ioannis; Zhang, Wei; Xu, Letian (Frontiers in Immunology, 2024)
Insects constitute approximately 75% of the world's recognized fauna, with the majority of species considered as pests. Entomopathogenic fungi (EPF) are parasitic microorganisms capable of efficiently infecting insects, rendering them potent biopesticides. In response to infections, insects have evolved diverse defense mechanisms, prompting EPF to develop a variety of strategies to overcome or circumvent host defenses. While the interaction mechanisms between EPF and insects is well established, recent findings underscore that their interplay is more intricate than previously thought, especially evident across different stages of EPF infection. This review primarily focuses on the interplay between EPF and the insect defense strategies, centered around three infection stages: (1) Early infection stage: involving the pre-contact detection and avoidance behavior of EPF in insects, along with the induction of behavioral responses upon contact with the host cuticle; (2) Penetration and intra-hemolymph growth stage: involving the initiation of intricate cellular and humoral immune functions in insects, while symbiotic microbes can further contribute to host resistance; (3) Host insect's death stage: involving the ultimate confrontation between pathogens and insects. Infected insects strive to separate themselves from the healthy population, while pathogens rely on the infected insects to spread to new hosts. Also, we discuss a novel pest management strategy underlying the cooperation between EPF infection and disturbing the insect immune system. By enhancing our understanding of the intricate interplay between EPF and the insect, this review provides novel perspectives for EPF-mediated pest management and developing effective fungal insecticides.